RAA-CRISPR/Cas12a-based visual field detection system for rapid and sensitive diagnosis of major viral pathogens in calf diarrhea - Chen, Junzhen; Wang, Yu; Aikebaier, Rezeguli; Liu, Haoran; Li, Yingxin; Yang, Li; Haiyilati, Areayi; Wang, Lixia; Fu, Qiang; Shi, Huijun (Frontiers in Cellular and Infection Microbiology, 2025)
Calf diarrhea is a complex digestive disorder in cattle that imposes significant economic losses in terms of calf mortality, growth impairment, and treatment costs. Both infectious and non-infectious agents contribute to its aetiology; however, most of the infectious cases are caused by viruses, often accompanied by severe co-infections. To identify viral culprits, we performed viral metagenomic sequencing on three pooled samples from the 150 diarrheal samples from Xinjiang, China, which helped with identification of the following four predominant agents: bovine nepovirus (BNeV), bovine coronavirus (BCoV), bovine viral diarrhea virus (BVDV) and bovine enterovirus (BEV). Currently, the process of diagnosing these pathogens involves time-consuming workflows, limited sensitivity, poor portability, and lack of field applicability. Keeping these diagnostic shortcomings in mind, an integrated platform called RAA-CRISPR/Cas12a system was developed by combining recombinase-aided amplification (RAA) at 37°C with CRISPR/Cas12a-mediated fluorescence detection, which achieved 100–100,000 times higher sensitivity than conventional polymerase chain reaction (PCR) (detection limits: 1–10 copies/μL) and demonstrated 100% specificity against non-target pathogens. Clinical validation of sensitivity and specificity of 252 samples revealed 1.6–4.9 times higher detection rates (239 positives) than PCR (81 positives), which was consistent with PCR-confirmed cases. The assay’s 40-min. workflow enables rapid on-site deployment without specialized instrumentation, as it requires only a portable heat block and blue LED transilluminator. Hence, with its laboratory accuracy and field applicability, this method helps in early identification of pathogens, outbreak containment and mitigation of economic loss in the global cattle industry.